Вплив легувальної добавки на теплофізичні та реологічні властивості полімерної композиції, що не містить галогенів, для ізоляції та оболонок кабелів - Золотарьов, Володимир Михайлович; Чулєєва, Олена Володимирівна; Чулєєв, Володимир Леонідович; Кулешова, Тетяна Анатоліївна; Суслін, Микола Сергійович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Попит на вогнестійкі композиції, що не містять галогенів, для виготовлення пожежобезпечних проводів та кабелів безперервно зростає. Тому розробка цих матеріалів є актуальною проблемою. Метою статті є дослідження впливу легувальної добавки на теплофізичні та реологічні властивості композицій. Теплофізичні властивості визначено з використанням приладу TGA/DSC 1/1100 SF компанії METTLER TOLEDO. Реологічні дослідження полімерних матеріалів проведено методом капілярної віскозиметрії на приладі ИИРТАМ. Визначено вплив легувальної добавки на формування надмолекулярної структури наповнених полімерних композицій. Встановлено зниження ефективної в'язкості розплаву полімерної композиції в 6 разів зі зростанням швидкості зсуву в 40 разів при зміненні температури від 150 до 190 ° С. Швидкість зсуву полімерної композиції з легувальною добавкою зростає в 40 разів з підвищенням напруження зсуву в 9 разів. Результати досліджень дають можливість обґрунтовано підходити до розроблення ефективних технологічних процесів виготовлення ізоляції та оболонок силових кабелів.

Introduction. The demand for halogen-free fire-resistant compositions for the manufacture of fire-retardant wires and cables is constantly growing. Problem. Therefore, the creation and further processing of these materials is an urgent problem. Goal. The aim of the article is to study the effect of the doping additive on the thermophysical and rheological properties of halogen-free compositions for power cables with voltage 1 kV with the determination of both the temperatures of phase and structural transformations of polymer compositions. Methodology. Experiments investigating the phase transformations were carried out with the help device of thermogravimetric analysis and differential scanning calorimetry TGA/DSC 1/1100 SF of METTLER TOLEDO company. Rheological studies of polymeric materials were conducted by using the method of capillary viscosimetry in the device IIRT–AM. Results. The influence of the doping additive on the formation of the supramolecular structure of the filled polymer compositions for cable products was determined, that resulted in the temperature increase of the decomposition beginning by 11 ° С and the end of decomposition by 7 ° С. Originality. The effect of a doping additive on reducing the effective melt viscosity of a polymer composition from 6·10⁴ to 1·10⁴ Pa·s with increasing shear rate has been shown for the first time. The shear rate of the polymer composition cont aining the doping additive in creases from 0.5 to 20 s﹣¹ with increasing shear stress. Practical value. The research results provide an opportunity to reasonably approach the development of effective technological processes for the manufac ture of the insulation and sheaths of power cables from halogen-free polymer compositions.
Influence of doping additive on thermophysical and rheological properties of halogen-free polymer composition for cable insulation and sheaths
Keywords: кабельна продукція; легувальна добавка; реологічні властивості; температура плавлення; температура початку розкладу; cable production; doping additive; rheological properties; melting temperature; decomposition onset temperature